2003
DOI: 10.1152/jn.00582.2002
|View full text |Cite
|
Sign up to set email alerts
|

Local Field Potentials and the Encoding of Whisker Deflections by Population Firing Synchrony in Thalamic Barreloids

Abstract: In layer IV of rat somatosensory cortex, barrel circuitry is highly sensitive to thalamic population firing rates during the first few milliseconds of the whisker-evoked response. This sensitivity of barrel neurons to thalamic firing synchrony was inferred previously from analysis of simulated barrel circuitry and from single-unit recordings performed one at a time. In this study, we investigate stimulus-dependent synchronous activity in the thalamic ventral posteromedial nucleus (VPm) using the more direct ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 39 publications
4
51
0
Order By: Relevance
“…These results are consistent with the multiunit recordings by Pinto et al (2000) and are comparable with the synaptic responses of barrel cortex neurons shown here [compare Fig. 6 A in Temereanca and Simons (2003) with our Fig. 6].…”
Section: Effect Of Increasing Stimulus Intensity On Synaptic and Spiksupporting
confidence: 92%
See 4 more Smart Citations
“…These results are consistent with the multiunit recordings by Pinto et al (2000) and are comparable with the synaptic responses of barrel cortex neurons shown here [compare Fig. 6 A in Temereanca and Simons (2003) with our Fig. 6].…”
Section: Effect Of Increasing Stimulus Intensity On Synaptic and Spiksupporting
confidence: 92%
“…Here, we chose to plot our measurements against velocity only and not acceleration, because this was the parameter that could be more accurately quantified (see Materials and Methods). We acknowledge that acceleration is also increasing and could in fact be the more important parameter (Temereanca and Simons, 2003) of the deflection determining the synaptic response. However, the main thrust of this work is not to characterize the cortical responses to either velocity or acceleration specifically but to understand the effect of increasing stimulus intensity (represented by the velocity-acceleration of the deflection) on the composition of synaptic responses in the different layers of the barrel cortex.…”
Section: E)mentioning
confidence: 97%
See 3 more Smart Citations